Traceable human experiment design research : theoretical model and practical guide - Mandran, Nadine (Advances in information systems set, 2018)
The aim of this book is to describe the methodology of conducting the THEDRE research "Traceable Human Experiment Design Research". It applies to Research in Human Centered Informatics (RICH). These are areas of computer research that integrate users to build scientific knowledge and supporting tools for this research. As an example, we can mention the relevant fields such as Information Systems (IS), Human Machine Interfaces (HMI) Engineering, and Human Information Systems (HIA). The construction of this language and method is based on experiments conducted since 2008 in the field of RICH.